Relationship Between Population Size and Habitat Area of Giant Pandas in China - Dongwei Kang (Animals, 2025)
This study analyzed survey result data of giant panda populations and habitats in the third and fourth giant panda surveys to reveal the population size–habitat area relationship and assess the habitat status at the county and nature reserve levels. Results showed that a significant linear relationship existed between the logarithm of population size (lnS) and the logarithm of habitat area (lnA), with an equation of lnS = 1.145 × lnA − 4.022. Based on this relationship, this study determined that 557.43 km2 was the minimum habitat area for maintaining a sustainable survival population of 25 pandas (the minimum population size to ensure sustainable survival with a relatively low extinction probability). This study selected 20 counties and 16 nature reserves containing ≥25 pandas and found that 30.0% of counties and 87.5% of reserves had habitat areas less than 557.43 km2. More habitat restoration efforts are needed to increase the habitat. The habitat area remained stable in the selected counties but decreased in the selected reserves between the third and fourth surveys. The causes of habitat decline in counties and reserves should be identified so that targeted conservation measures can be implemented. This study provides a theoretical basis and scientific reference for giant panda conservation and habitat management.